Soroprevalência da linfadenite caseosa em caprinos (Capra hircus) oriundos de um abatedouro do município de Mossoró, Rio Grande do Norte. - Fernandes, Maria da Conceição Rodrigues (Universidade Federal Rural do Semi-Árido, 2020)
Caseous lymphadenitis (CLA) is a chronic zoonosis that affects small ruminants worldwide, with a clinical picture characterized by the development of abscesses in the internal organs and / or superficial lymph nodes. However, many subclinical cases occur, and its control tends to be difficult, since in most cases, such cases are only identified in post-mortem inspection. Thus, the serological diagnosis appears as an alternative in the early detection of LC due to its high sensitivity. In this context, it was proposed to conduct a seroprevalence study in goats from a slaughterhouse in the city of Mossoró / RN. For this purpose, 150 goat blood samples were collected and processed for indirect ELISA with Corynebacterium pseudotuberculosis culture supernatant. Associated with this, the collection of fragments of internal organs suspected of infection by C. pseudotuberculosis was performed after slaughter for microbiological characterization. The ELISA was able to detect an equivalent to 13.3% (20/150) positive animals. Among the positive goats, 90% were females. Microbiological characterization identified 2% (3/150) positive animals from liver and lung samples that presented abscesses suggestive of LC. It was possible to identify the association between the variables age and seropositivity, as well as sex and seropositivity, respectively. Regarding the two diagnostic techniques, the kappa index revealed a weak agreement (k = 0, 344), and the ELISA technique proved to be practical and sensitive, denoting the feasibility to be used in disease control programs
Monografia
Keywords: Linfadenite Caseosa; Corynebacterium pseudotuberculosis; Caprinos; ELISA indireto; Nordeste; Caseous lymphadenitis; Corynebacterium pseudotuberculosis; Goats; Indirect ELISA; Northeast; CIENCIAS BIOLOGICAS::BIOTECNOLOGIA